Mapping Barriers and Opportunities: Advancing Inclusive Service Delivery for Autistic Children in Kelantan - Ruzaini, Ijon; Azizul, Ahmad; Yohan, Kurniawan; Nik Ahmad Farhan, Azim @ Nik Azim; Fairuz A'dilah, Rusdi; Azahah, Abu Hassan Sha'ari; Siti Amirah, Ahmad Tarmizi; Tarmiji, Masron; Asykal Syakinah, Mohd Ali (2026)
This study investigates the spatial distribution of Autism Spectrum Disorders (ASD) in Kelantan, Malaysia, with the aim of improving service delivery and advancing social justice in the care of autistic children. Kelantan, a predominantly rural state, faces persistent disparities in healthcare access, making it an ideal context for examining inequities in diagnosis and intervention. Using data from 103 ASD cases recorded between 2022 and 2024 at two major autism centers, we employed Geographic Information Systems (GIS) tools (including Global Moran’s I, Getis-Ord Gi*, mean center, Standard Deviational Ellipse (SDE), and Local Indicators of Spatial Association (LISA) to identify spatial clustering patterns of severe, mild, and high-functioning ASD. The findings indicate that the selected analysis effectively visualises pertinent information for the autism community in Kelantan and facilitates the planning of comprehensive intervention strategies for this population. From a social work perspective, these findings highlight the potential of GIS mapping to reveal inequities in service provision. GIS results can support cross-sector collaboration among healthcare providers, educators, and planners, and inform advocacy for policies that expand diagnostic outreach and resource distribution in underserved areas. By integrating spatial evidence with principles of inclusion and social equity, this study demonstrates how GIS mapping can guide interventions to close service gaps, strengthen community-based support systems, and foster safer, more nurturing environments for children with ASD and their families in Kelantan.